Класифікація синергетичного ефекту при диверсифікації господарської діяльності - Брінь, Павло Володимирович; Прокоп, Микола Вікторович; Пожидаєва-Литвиненко, О. В. (Видавничий дім "Гельветика", 2021)
У статті розглядається питання синергії, синергетичного ефекту та класифікації синергії відносно різних класифікаційних ознак. Сутність синергії досліджено з моменту використання цього поняття в економіці та менеджменті дотепер. Особливу увагу приділено зв’язку ефекту синергії та диверсифікації господарської діяльності, взаємовпливу підрозділів різних стратегічних зон господарювання диверсифікованої компанії. Авторами вдосконалено існуючі методичні засади класифікації синергетичного ефекту шляхом обґрунтування низки нових класифікаційних ознак та виділення видів синергії відповідно до цих ознак. На відміну від існуючих підходів до класифікації синергетичного ефекту запропонована класифікація має багаторівневу структуру, яка дає змогу більш докладно аналізувати феномен синергії для підприємств різних галузей економіки.

The article deals with the issues of synergy, synergy effect and classification of synergy by various characteristics. The paper also analyzes the essence of synergy from the introducing of this concept into economics and management sphere up to the present time. The particular attention is paid to the relationship between the effect of synergy and diversification of economic activities, the mutual influence of different strategic business units of the diversified company. One of the modern trends in management is increasing the efficiency of the enterprise through diversification; diversification can be divided into related and unrelated; related diversification means entering a new area of activity that is associated with existing businesses of the company; unrelated diversification refers to a new type of activity that has nothing similar with previously organized areas of business. In turn, related diversification can be divided into vertical and horizontal. Vertical diversification occurs when the company goes back to previous stages of its production cycle or moves forward to subsequent stages of the same cycle. Horizontal diversification strategy involves the acquisition or development of new products that can be sold to the current customers of the company. In this strategy the company relies on the existing level of sales and production technology. At the same time, new products can be produced under an existing brand. This allows the company to promote quickly its products to new markets with less risk. The synergy effect during diversification means that diversifying company into a new business should offer potential for the company’s existing strategic business units and the new business to perform better together within one corporation than they would perform operating as independent units. The authors have improved the existing methodological foundations for the classification of the synergy effect by providing of a number of new classification features. In contrast to the existing approaches to the classification of the synergistic effect, the proposed classification has a multi-level structure, which allows a more detailed analysis of the phenomenon of synergy for enterprises in various sectors of the economy. Usage of the proposed classification approach should simplify for the management of enterprises choosing possible ways of increasing the efficiency of economic activity through implementing of synergy.
Classification of synergy effect in diversification
Keywords: синергія; конкурентоспроможність підприємств; економіка; менеджмент; synergy; diversification; strategy; enterprise competitiveness